Conversations on “Community Lawyering”: The Newest (Oldest) Wave in Clinical Legal Education - Karen Tokarz; Nancy L. Cook; Susan Brooks; Brenda Bratton Blom (Washington University Journal of Law & Policy, 2008)
In this Essay, we will explore the pedagogical and professional challenges and rewards of community lawyering and clinical legal education. The authors are clinical law faculty who self-identify as community lawyers and teachers of community lawyering clinics. We have gathered in recent years with a larger group of similarly engaged colleagues to discuss what we mean by community lawyering, how we teach it, and how we practice it. This Essay seeks to capture some of those conversations, crystallize some of the ideas that have arisen out of the discussions, and examine the implications of these ruminations for future directions in clinical legal education.
Keywords: Clinical legal education; Social movements; Restorative justice; Access to justice; Community lawyering; Client development; Public interest law; United States